The Role of Feedback Training on Early Postoperative Recovery and Anxiety Scores in an Ambulatory Surgical Unit: A Secular Trend Study - Dukhan Alexander; Yusupov Teymur; Kabra Naama; Ezri Tiberiu; Boaz Mona (The Journal of Critical Care Medicine)
We used a ten-item postoperative quality of recovery score (QoR-10) to assess the perioperative quality of care in an in-hospital ambulatory surgical unit.